Literature Survey on High Performance Concrete Using GGBS and Robosand (M50grade) - Dr. M. M. Vijayalashmi, L. S. Indra Sena Reddy (International Journal of Advanced Science and Technology, 2020)
The utilization of tip top solid gives central focuses in strength, straightforwardness of course of action, and blurred yank and shrinkage, essentially as raised compressive, shear and flexibility. Adjusting these central focuses are likely diminished adaptability and impenetrability to chimney, and improved unit charge. The blessing paper offices around the investigating properties of M50 grade concrete with midway superseding of cement with Ground Granulated Blast Furnace Slag (GGBS) and sand with the ROBO sand (smasher earth). The 3-D shapes and chambers are endeavored for compressive qualities and split flexibility. It is found that by method for the fragmentary supplantings of cement with GGBS and the sand with ROBO sand helped in improving the high-caliber of the solid liberally diverged from apparent mix concrete. The compressive incredible is found at 7days, 28 days. Water decreasing admixtures are used to build the convenience attributes.